Sensorial evaluation of continuously fermented beer and the role of process parameters in adjusting its flavour profile - Brányik, Tomáš (2005)
Although traditional batch overwhelmingly prevails over continuous fermentation, a breakthrough in quality and savings could be achieved by a simple, flexible and cheap fermentation system. This work deals with a complete continuous beer fermentation consisting of an airlift and a packed-bed reactor containing yeast immobilized on spent grains and corncobs, respectively. The goal was to study the influence of process parameters on bioreactor performance and flavour profile of beer. Consumers considered the continuously fermented beer to be of a regular quality. The possibility of flavour adjustments by changing the process parameters was proved by a panel of experienced tasters.